Non-take-up by “non-proposition“: Discussion on an under-documented research perspective - Antoine Rode (Culture, Practice & Europeanization)
Non-take-up, describing the situation in which an eligible person does not benefit from one or more rights to which he or she is entitled, is a topic of growing interest in most European welfare states. A large volume of literature now documents the phenomenon well. Statistical studies agree that non-take-up is a widespread problem across countries with very different welfare state systems. Studies on non-take-up also identified, very early on, the main determinants of the phenomenon and developed theoretical models of non-take-up. Most of this literature is based on a traditional economic perspective or a behavioural economic perspective. This paper contributes to the debate on the determinants of the phenomenon, by focusing on a specific type of non-take-up, which is under-researched. This is the situation of “non-proposition”, in which the provider does not propose a benefit to the potential claimant. This paper is based on a study conducted in France on a benefit intended for people with disabilities. We show that analysing these situations raises issues that are different from other determinants of non-take-up. These situations enable us to examine the practices of the social service professionals, their values and their professional skills. Non-take-up by “non-proposition” carries potential risks, when it lengthens the time it takes to access rights or when it renders social needs invisible. However, the professionals may have “good reasons” for not proposing assistance and/or benefits.